Pengaruh Kemampuan Personal, Pelatihan Kerja, dan Keterlibatan Pemakai terhadap Kinerja Sistem Informasi Akuntansi - Pradnyana, I Gede Made Aditya; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 25 No 2 (2018), 2018)
The performance of the Accounting Information System is a benchmarks for the success of a company. With the existence of an accounting information system, it is expected that an employee is able to provide and fulfill information needs in a timely, accurate and trustworthy manner. This research was conducted in order to know the influence of personal ability, job training, and the involvement of users in the accounting information system performance. This research was conducted at PT Bank Rakyat Indonesia Denpasar branch of Gajah Mada. This study used 77 respondents with purposive sampling method. Data analysis technique used is multiple linear regression analysis. Based on the results of this study indicate that personal ability is useful in improving the performance of accounting information systems. Job training is useful in improving the performance of accounting information systems. User involvement is useful in improving the performance of accounting information systems. Keywords : performance of accounting information systems, personal capabilities, job training, and user involvement